Legal Certificity in The Transformation of Conventional Land Certificates to Electronic Land Certificates - Raina Fishecella; Hanifah Febriani (Proceeding International Conference Restructuring and Transforming Law, 2026)
The implementation of electronic land certificates based on Regulation of the Minister of ATR/BPN Number 3 of 2023 aims to improve the efficiency of land governance through digitalization. This research uses an empirical legal approach with descriptive analytical specifications at the Karanganyar Regency Land Office. Since July 2024, 36,039 electronic certificates have been issued through physical and legal data validation in the Computerized Land Activities (KKP) system. Legal protection for owners is guaranteed through electronic signatures (BSrE) and cryptographic features that have valid evidentiary power according to the ITE Law. Although this system minimizes the risk of duplicate certificates and data manipulation, technical network constraints and low digital literacy remain major obstacles during the transition period. Electronic certificates strengthen legal certainty and land data security. Their success depends heavily on consistent data validation, reliable cybersecurity systems, and intensive public outreach.